2018
DOI: 10.24200/jeps.vol12iss4pp708-723
|View full text |Cite
|
Sign up to set email alerts
|

Could Resilience and Flourishing be Mediators in the Relationship between Mindfulness and Life Satisfaction for Saudi College Students? A Psychometric and Exploratory Study

Abstract: In There are few Arabic studies examining the disposition of mindfulness, resilience, and well-being of college students. The purpose of the present study is to examine the factor structure and internal consistency of the Arabic version of mindful attention awareness scale (MAAS) and the brief resilience scale, and to test a model that describes the role of resilience and well-being, in relation to mindfulness and life satisfaction. For this reason, a study of two folds was conducted with the assistance of Umm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 82 publications
1
7
0
1
Order By: Relevance
“…Moreover, it has been proposed as an indicator of well-being encompassing the experience of feeling joy, contentment, or happiness in life (i.e., hedonic well-being) as well as having an effective psychological functioning (i.e., eudaemonic well-being; Huppert and So, 2013). In fact, flourishing is related to less burnout and higher levels of health, life satisfaction, and work engagement (Garzón-Umerenkova et al, 2018;Younes and Alzahrani, 2018;Freire et al, 2020;Imran et al, 2020). Although this variable has not been extensively studied in adolescents (Witten et al, 2019), and even less in relation to academic performance, some studies suggest that higher levels of flourishing may contribute to a better academic performance and a greater likelihood of prioritizing academic chores (Datu, 2018;Datu et al, 2020).…”
Section: Flourishing As Mediatormentioning
confidence: 99%
“…Moreover, it has been proposed as an indicator of well-being encompassing the experience of feeling joy, contentment, or happiness in life (i.e., hedonic well-being) as well as having an effective psychological functioning (i.e., eudaemonic well-being; Huppert and So, 2013). In fact, flourishing is related to less burnout and higher levels of health, life satisfaction, and work engagement (Garzón-Umerenkova et al, 2018;Younes and Alzahrani, 2018;Freire et al, 2020;Imran et al, 2020). Although this variable has not been extensively studied in adolescents (Witten et al, 2019), and even less in relation to academic performance, some studies suggest that higher levels of flourishing may contribute to a better academic performance and a greater likelihood of prioritizing academic chores (Datu, 2018;Datu et al, 2020).…”
Section: Flourishing As Mediatormentioning
confidence: 99%
“…Since it was seen in the evaluation of the distribution of the nursing students' scores on the MAAS and SWLS that their scores on MAAS were not normally distributed, medians were assessed. The median score of the students on the MAAS was 56 (50-64); the median of their scores on the SWLS was 15 (12)(13)(14)(15)(16)(17) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A study with Saudi students revealed that mindfulness had an effect on satisfaction with life, albeit not to a great extent. 16 Studies conducted with university students in Spain point to a positive correlation between mindfulness and satisfaction with life. 28,34 University students in South Africa participated in a study where it was found that mindfulness levels had a positive effect on satisfaction with life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations